Мой серый друг: рассказы русских писателей / [Б. С. Житков, А. П. Чехов] - Фомин Н. (Лапы, крылья и хвосты, 2012)
Экземпляры: ф.14 (2012) / Инвентарный номер: 54829 / Цена: 260.42 / Сис.шифр: 84(2Рос=Рус)-4 / Авт.знак: М 74 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)-4